Efficacy of World Health Organization-Recommended Homemade Hand Sanitizer Against Bacteria and Fungus - Moehamad Orliando Roeslan; Mario Richi; Aradhea Monica Drestia; Armelia Sari Widyarman (Journal of Indonesian Dental Association, 2021)
Introduction: Handwashing is among the best practices to prevent the transmission of various diseases especially during the pandemic. Handwashing with soap can reduce respiratory tract infections. The World Health Organization (WHO) released guidelines for making homemade hand sanitizer. Objective: This study aimed to analyze the effectiveness of antibacterial hand- rub, as recommended by WHO, containing ethanol, hydrogen peroxide, and glycerol in varying concentrations against bacteria and fungus. Methods: This experimental laboratory study was designed to assay the efficacy of hand sanitizer ingredients—96% ethanol, 3% hydrogen peroxide, and 98% glycerol, as recommended by WHO—against Escherichia coli, Staphylococcus aureus, and Candida albicans. Commercial hand rubs were used in this study for comparison. Result: Minimum inhibitory concentration (MIC) testing showed that the WHO hand rub at 25% concentration inhibited E. coli and S. aureus growth, while 12,5% concentration inhibited C. albicans. Conclusion: The WHO-recommended homemade hand sanitizer containing ethanol, hydrogen peroxide, and glycerol at a concentration of 50% is effective in eliminating Escherichia coli, Staphylococcus aureus, and concentration of 25% is effective on Candida albicans. Further study is needed to analyse these materials against other bacteria and viruses.